Reduced graphene Oxide/NiO based nano-composites for the efficient removal of alizarin dye, indigo dye and reduction of nitro aromatic compounds - Renu Verma; Manmohan Singh Chauhan; Saurabh Pandey; Anshu Dandia (Heliyon, 2023)
Removal of alizarin red S (ARS) and Indigo dye from aqueous media and reduction of nitro aromatic compounds are successfully done under mild condition by using reduced Graphene Oxide-Nickel Oxide (rGO-NiO) nanocomposite as catalyst. RGO-NiO is well characterized by different analytical techniques. Morphology, structural, and composition studies done by HRTEM, FESEM, EDX, TGA, FTIR, XPS, Raman spectroscopy, and XRD. RGO-NiO nanocomposite has high stability for the removal of ARS, Indigo dye, reduction reaction nitro aromatic compounds.